Hypergastrinemia in Children : A Case Report - Edbert Wielim; Nielda Kezia Sumbung; Ariani Dewi Widodo (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Gastrin is an important hormone in the gastrointestinal system that promotes gastric acid secretion. Gastrin hormone is produced by the G-cells in the antrum of the stomach. Besides stimulating gastric acid secretion, gastrin also induces the proliferation of the gut epithelial cells, tissue remodelling, and angiogenesis. Gastrin levels higher than 100-150 pg/ml are known as hypergastrinemia. Hypergastrinemia may cause the hypersecretion of stomach acid, which, if not treated properly, may leads to refractory peptic ulcer, severe gastroesophageal reflux disease (GERD), diarrhea, or death due to complications of refractory peptic ulcer. This case presented a 12 years old boy with a chief complaint of severe epigastric pain in the past month, accompanied by nausea, especially during supine position. The patient had a previous history of esophagitis. He showed no significant changes upon empirical PPI treatment. However, slight improvements were observed after the administration of Helicobacter pylori treatment. The gastrin level in this patient was 198 pg/mL. Upon discharge, the patient was still given PPI treatment. During the follow-up visitation, patient complaints had improved significantly, and the patient was planned to undergo routine evaluations of gastrin.